An Operator Semigroup in Mathematical Genetics - Bobrowski, Adam (Springer, 2015)
This authored monograph presents a mathematical description of the time evolution of neutral genomic regions in terms of the differential Lyapunov equation. The qualitative behavior of its solutions, with respect to different mutation models and demographic patterns, can be characterized using operator semi group theory.